Experiência de produção agroecológica do Grupo Resistência Camponesa, localizado no Assentamento Guanabara de Imbaú - PR - Silva, Karina Alves Umbelino da (2017)
With the advent of modernization in the field since 1960, Brazil is experiencing a new phase, sustained by high technology and openness to large multinationals. The Green Revolution project that was often called necessary today is reflected in the search of peasants for alternative work and stay in the field. What was posed as a solution to hunger in Brazil, left only consequences that mark the environmental issues, the social and economic relations of the country. It is for these reasons, that since 1980, it has led the subjects of the field to be built within organized movements in the quest to reconquer the land. The Movement of the landless (MST) emerges in this period and throughout its history seeks to build a constant dialogue between its work with the land and agroecology. In this sense, the research has the initiative to report on the agroecological production experience of the peasant resistance group, located in the Guanabara Settlement of Imbaú - PR, a group composed of 10 families that took the challenge of agroecological production in their properties. The work is composed by a bibliographical review and the investigations were done from questions, observation and as a listener of the meetings and courses that the group Resistance Peasant participated. Therefore, the production of healthy food in the Agrarian Reform Settlement areas is the result of a concrete need of the subjects to strengthen the dialogue about a technological and productive matrix that is sustainable and that respects the socio-environmental relations as a whole. The Peasant Resistance group represents agroecology and demonstrates that in fact it happens in the Settlement, and that every day advances in its production and strengthen the fight against agribusiness.